If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + -1(3x + -7) = 23 Reorder the terms: 11x + -1(-7 + 3x) = 23 11x + (-7 * -1 + 3x * -1) = 23 11x + (7 + -3x) = 23 Reorder the terms: 7 + 11x + -3x = 23 Combine like terms: 11x + -3x = 8x 7 + 8x = 23 Solving 7 + 8x = 23 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 8x = 23 + -7 Combine like terms: 7 + -7 = 0 0 + 8x = 23 + -7 8x = 23 + -7 Combine like terms: 23 + -7 = 16 8x = 16 Divide each side by '8'. x = 2 Simplifying x = 2
| 7x+5x-5=3(4x+1) | | 7x-14=3x+18 | | 2x-7=6-6x-2x | | 32/x=x/2 | | 60x-30=15(4x-2) | | (63+9)/3 | | 490=7n | | 3/49=26/7x | | 15z^2+14z-8=0 | | -2y^2+1y+10=0 | | 6(y)-13=-13 | | x^2+8x-12=x^2 | | p-1=5p-8+3p | | 47x+94=47x+81 | | 8.3=4(k)-2.5 | | x^2+8-12=x^2 | | 3+3(2x-1)=14+4x | | 4x-16/3x-12 | | 16m+15m^2-15= | | 3(p)-14=9 | | 7(t)-20=33 | | -14=10-2x | | 8z+12z=5z-21 | | 3x+x+4=8x-4x+4 | | 5(w+4z)-5(w+3)=8 | | 4+6r-r=-5+8r | | x+9=-17 | | 10x+x=196 | | (1/4)(p)+6=8 | | 6x+39x-7=9(5x+6) | | 4x-10=14+x | | 35=7(z)-7 |